2018
DOI: 10.1111/jch.13155
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure during emergency departments visit is associated with increased rate of hospitalization for heart failure: A retrospective cohort study

Abstract: There is a limited literature discussing the long-term outcome of patients admitted to the emergency department with elevated blood pressure. The aim of the present study was to evaluate outcomes of patients with hypertension who attended an emergency department. All patients with hypertension who attended an emergency department without target organ damage were evaluated. A composite end point at 18months, which included all-cause mortality, acute coronary syndrome, cerebrovascular accident, or hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Several clinical studies have evaluated the impact of blood pressure on clinical outcomes in patients with ACS other than death. A retrospective cohort study found that, compared with those with normal blood pressure, those with elevated blood pressure during ED visits were associated with an increased risk of hospitalization due to heart failure 19 . Lower blood pressure in ACS patients was signi cantly associated with an increased risk of hospitalization for cardiovascular events 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have evaluated the impact of blood pressure on clinical outcomes in patients with ACS other than death. A retrospective cohort study found that, compared with those with normal blood pressure, those with elevated blood pressure during ED visits were associated with an increased risk of hospitalization due to heart failure 19 . Lower blood pressure in ACS patients was signi cantly associated with an increased risk of hospitalization for cardiovascular events 20 .…”
Section: Discussionmentioning
confidence: 99%
“…1,10,30 Several relevant risk factors for poorer HF prognosis have been reported and those were confirmed in our study. 13,[31][32][33][34][35][36][37][38][39] The MADIT II (Multicenter Automatic Defibrillator Implan tation Trial II) cohort analysis identified re nal failure as one of the strongest predictors of poor prognosis. 35 Gheorghiade et al 36 and Ambrosy et al 37 listed renal failure and low systolic blood pressure among factors influ encing the prognosis of patients hospitalized for HF.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…In a study from Israel, Ayalon‐Dangur and colleagues evaluated the outcome of patients with hypertension who visited emergency departments (ED) over an 18‐month period. They included all patients with hypertension attending an ED who had no target organ damage.…”
Section: Introductionmentioning
confidence: 99%